Queuing solution without application installation for service oriented industry - Ng, Wan Qing (2019)
Queue is highly related to human society and it can be observed in everywhere. A proper queue management system can help to reduce queue length, average waiting time, dropout rate and optimise the usage of the resources. In addition, a queue without a proper queue management system will waste the time of people. This is because people will need to wait in line and do nothing while waiting for their turn. However, queue management system is seldom be used in small business like the hawker and beauty salon due to the high operation and entry cost of the existing queuing solutions. Besides that, most of the existing queuing solutions still need their customers to be physically present. These queuing solutions have no value to small business. Apart from these, most of the existing queue management systems are focus on the large and medium organization, so the prices will be too high for the small business and the system will be too complex or not applicable for the small business. Therefore, a queue management system that can save the time of the customers by allowing them to leave the queuing area and only inform them to come back when their turn is near will be developed at the end. Furthermore, the system must be affordable and suitable for the small business service providers. In a word, this report is about to develop a comprehensive and affordable queuing solution for the small business. In addition, the queuing solution developed in this report also allows the customers to leave the queuing area and make use of the waiting time to do some productive tasks. On the other hand, this queuing solution was tested by using smart phones and computer web browser under the Wi-Fi condition. In conclusion, this report has proven that a queue management system can work without application installation and it can still allow the customers to leave the queuing area and only come back when their service is ready or when their turn is near.